0254 Association of Slow Wave Activity and Odds Ratio Product with Internalizing and Externalizing Problems in Children and Adolescents. (25th May 2022) - Fernandez-Mendoza, Julio; Ricci, Anna; He, Fan; Calhoun, Susan; Fang, Jidong; Younes, Magdy; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward
Abstract: Introduction: The association of metrics of sleep microstructure with internalizing and externalizing problems in youth has remained elusive. While one study found increased frontal slow wave activity (SWA) in depressed adolescents, there is lack of evidence for a relationship between dimensional measures of behavior and metrics of sleep depth/intensity. We examined the association between two measures of sleep depth/intensity, slow wave activity (SWA) and odds ratio product (ORP), with internalizing and externalizing problems in children and adolescents. Methods: We calculated SWA and ORP during non-rapid eye movement (NREM) sleep at central, frontal and fronto-occipital derivations in 639 children (5-12y, median 9y) and 418 adolescents (12-23y, median 16y) from the Penn State Child Cohort via in-lab polysomnography. ORP provides a standardized measure of NREM sleep depth, while ORP-9 (average ORP in the 9-seconds following NREM arousals) provides a metric of arousability. SWA (0.4-4Hz) absolute power (µV2) was determined during NREM sleep. Internalizing and externalizing problems were assessed on Achenbach's Behavior Checklist by parent (subjects≤17y) or self-report (subjects≥18y). For each scale, T-scores with a mean of 50 and standard deviation of 10 were obtained following standardized scoring. Multivariable-adjusted linear regression models examined the association between SWA/ORP and clinical outcomes. Results: At ages 5-12, fronto-occipital SWA was negatively associated with externalizing behaviors (p=0.05), while fronto-occipital and frontal ORP, and frontal ORP-9 were positively associated with internalizing symptoms (all p<0.01). At ages 12-23, central SWA was negatively associated with internalizing symptoms (p=0.05), while central (p=0.05) and frontal (p=0.03) ORP and central ORP-9 (p=0.03) were positively associated with externalizing behaviors. Conclusion: Reductions in SWA in childhood or adolescence are associated with developmentally appropriate behavioral problems, as depression/anxiety are more prevalent in adolescence. In contrast to SWA, increased ORP (lighter sleep) and ORP-9 (greater arousability) are associated with more anxiety/depression in childhood, yet more externalizing behaviors in adolescence. These distinct associations, such as SWA with externalizing behaviors and ORP with internalizing symptoms during childhood, may reflect how SWA captures local/synaptic control, while ORP global/state control, of sleep depth, making both sleep EEG biomarkers important from a developmental standpoint. Support (If Any): National Institutes of Health (R01MH118308, UL1TR000127)